Sociological Analysis of Construction Initiatives in Landless Communities: Practices of Gorkha Earthquake in Nepal - Adhikari, Shukra Raj; Chongbang, Nirmal; Bhatta, Deepak Raj; Shrestha, Birendra; Gautam, Mohan; Neupane, Bikash; Bhandari, Manoj (International Research Journal of Parroha, 2024)
Earthquake disaster is burning issue of the world including Nepal. It has became crucial phenomenon of global society. In this context his research paper examines the sociological aspects of earthquake disaster-resilient housing construction initiatives in landless communities affected by the 2015 Gorkha earthquake in Nepal. It highlights the significant outputs and outcomes of local housing strategies that leverage indigenous materials, knowledge, and social support. Utilizing a descriptive research methodology, data was gathered through close-ended and open-ended questionnaires, case studies, and field observations across various impacted communities. Secondary data sources included existing literature on landless housing reconstruction and community-based initiatives. The findings reveal that the landless communities suffered greatly due to seismically vulnerable structures, lack of preparedness, and insufficient use of critical seismic features. These communities often lack access to vital information that could mitigate disaster risks. The study further explores how residents have innovatively rebuilt their homes by integrating safety measures, utilizing salvaged materials, and combining traditional knowledge with scientifically validated techniques. This approach not only addresses immediate housing needs but also fosters long-term resilience against future disasters.